Prescription pattern of patients admitted in the intensive care unit of a tertiary care hospital in Puducherry, India: a cross sectional study - Maharani, B.; Jafrin, A. Lourdu; Prakash, M.; Priyadarshini, P. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Patients with varied demographic characteristics, admission criteria and heterogeneous group are admitted to medical Intensive Care Unit (ICU) and are usually associated with co-morbid illnesses. Instituting rational pharmacotherapy is the need of the hour for saving the life of critically-ill patients while irrational drug use may be life threatening. Drug use patterns and prescribing behaviour are the essential tools to measure drug use in health care facilities. Methods: A record based, cross-sectional, observational study was done at medical ICU, IGMC and RI, Puducherry after obtaining IEC approval. Systemic random sampling was followed and data was collected for a period of one year. Data were analysed based on demographic characteristics, prescribing pattern and WHO drug use indicators. Results: The data of 151 patients were analysed. Mean age of the patients admitted in ICU was 52.9±17.7 years. Percentage of male patients (57.6) admitted in ICU were more when compared to female patients (42.4). Infective etiology was the most common factor for ICU admission followed by cardiac disorders. Diabetes mellitus and hypertension were the most common co-morbidities. The average length of stay in ICU was 4.11±2.99 days. Duration of stay in ICU ranged from 1-5 days (78.8% patients) to 15-20 days (0.1% patients). On an average 10.6±4.3 drugs were prescribed for each patient. Percentage of drugs prescribed by generic name was 45.8%. Majority of the drugs (87.4%) were from essential medicine list. Antibiotics in the prescription was 13.8% and 44.4% of drugs were administered in parenteral route. The prescription was complete in 145 case sheets (96%). Majority of the patients (68.9%) were discharged with improvement in the condition for which they were admitted. Conclusions: This drug utilization study has highlighted the strengths and shortcomings of the prescription pattern of patients who were admitted in the critical care setup. The information derived from this research work will be transmitted to the stakeholders for implementing the modifications wherever applicable for the betterment of the patient and the community.